NILAI-NILAI TASAWUF DALAM TRADISI PERNIKAHAN MASYARAKAT BANJAR DI DESA TATAH PEMANGKIH LAUT KECAMATAN KERTAK HANYAR KABUPATEN BANJAR - Fadhel Muhammad (Jurnal Shaf, 2025)
The wedding tradition of the Banjar community in Desa Tatah Pemangkih Laut, Banjar Regency, is a cultural heritage that combines customary practices with Islamic spiritual values, particularly Sufism. This study aims to examine the implementation of the tradition and the Sufi values embedded in each stage of the wedding procession. A qualitative descriptive method was used through observation, interviews, and documentation. The findings show that the wedding procession includes basasuluh, batatakun, badatang, bapapayuan, meantar jujuran, bapingit, batimung, bepapai, berias and bepacar, batamat al-Qur’an, maarak pengantin, betatai, and bailang pengantin. Each stage contains Sufi values such as trust in God tawakal, spiritual vigilance muraqabah, humility tawadhu, gratitude syukur, self-purification tazkiyatun nafs, reflection tafakkur, love mahabbah, and Islamic brotherhood ukhuwah islamiyah, making marriage not only a physical bond but also a spiritual path. Thus, this tradition serves as a medium for internalizing Sufi teachings in family life.